Seroprevalance of toxocara antibodies in multiple sclerosis and ankylosing spondylitis [2] - Kuk, Salih; Ozgocmen, Salih; Bulut, Serpil (Medknow Publications and Media Pvt. Ltd, 2006)
[Abstract Not Available]
Keywords: HLA B27 antigen; protozoon antibody; adult; ankylosing spondylitis; autoimmune disease; central nervous system; clinical article; confidence interval; controlled study; demography; female; human; letter; male; medical research; multiple sclerosis; seroprevalence; Toxocara; Toxocara canis; toxocariasis